LEGAL INTROSPECTION TOWARDS THE DEVELOPMENT OF RIGHT TO PRIVACY AS FUNDAMENTAL RIGHT IN INDIA - Thaorey, Payal (Indonesia Law Review, 2021)
Privacy of the individual is an essential aspect of dignity. The ability of the individual to protect a zone of privacy enables the realization of the full value of life and liberty. Liberty has a broader meaning of which privacy is a subset. All liberties may not be exercised in privacy. Yet others can be fulfilled only within a private space. Privacy enables the individual to retain the autonomy of the body and mind. The autonomy of the individual is the ability to make decisions on vital matters of concern to life. The journey of right to privacy has been significant in India, from being completely ignored during the drafting of the Indian constitution till recognising it as one of the essential component of right to life of an individual. This development can be measured in the case by case development of ‘right to privacy’ by the Indian judiciary. Further at times, the law making bodies along with the judiciary has taken cognizance of the reflections of contemporary social and technological changes on the individual’s right to privacy. This paper will focus on the evolution of the concept of Privacy and its inclusion under the Constitution of India under Part III as a fundamental right. The paper will also discuss the understanding and application of right to privacy with reference to the technological developments and social media in India.